Design of a Nonlinear Variable-Gain Fuzzy Controller for FACTS Devices - Dash, P.K.; Morris, S.; Mishra, S. (2004)
The paper presents the design of a nonlinear variable-gain fuzzy controller for a flexible ac transmission systems (FACTS) device like the unified power flow controller (UPFC) to enhance the transient stability performance of power systems. The fuzzy controller uses a numerical consequent rule base of the Takagi-Sugeno type, which can be either linear- or nonlinear-producing control-gain variation over a very wide range; This type of fuzzy control is expected to be more robust and effective in damping electromechanical oscillations of the power systems in comparison with the conventional PI regulators used for UPFC control. Computer simulation results validate the superior performance of this controller.